EFFECTIVENESS OF EXTRACORPOREAL SHOCK WAVE THERAPY ON FOOT FUNCTIONAL ABILITY WITH PLANTAR FASCIITIS - Dewi, Navita Sekarsari; Agustina, Dwi; Nasirudin, Yusuf; Aminoto, Toto (Universitas Riau Kepulauan, 2023)
Background: Plantar fasciitis is a fascia inflammation characterized by symptoms of severe pain in the heel caused by microtrauma to the plantar fascia. Extracorporeal shock wave therapy (ESWT) and plantar stretching exercise (PSE) are two physiotherapy intervention strategies that can be used to treat plantar fasciitis. Method: This study was conducted at Poltekkes Jakarta 3 in March-May 2023 using a quasi-experimental method with two groups pre-posttest with a control group design. The sample size was 28 persons, divided into two groups of 14 people each, the intervention and control groups, and chosen using the purposive sampling method. The dependent variable was the foot functional ability of the as measured by the Foot Function Index (FFI). The independent variables were ESWT and PSE intervention in the intervention group and PSE in the control group. Data analysis consisted of univariate and bivariate with paired sample t-test and independent t-test. Results: The mean FFI values in the intervention and control groups before and after intervention were 44.44, 18.17, 47.80, and 32,13, respectively. The probability value of the paired sample t-test results in the intervention and control groups was 0.000, while the independent t-test results before the intervention were 0.606 after 0.002. Conclusion: The provision of ESWT intervention plus PSE was more effective than PSE alone in improving the functional ability of the feet in plantar fasciitis sufferers.